问题已解决
(EBIT-6 000×6%) ×( 1-25%)/(3 000 + 600) = ( EBIT-6 000×6%-2 400×8%) ×(1 - 25% )/3 000,我想知道計(jì)算過程
![](https://member.chinaacc.com/homes/resources/images/home/avatar/9.jpg)
![](/wenda/_nuxt/img/iconWarn.60bd4fe.jpg)
![](https://pic1.acc5.cn/011/59/92/01_avatar_middle.jpg?t=1676104611)
你好
(EBIT-6 000×6%) ×( 1-25%)/(3 000 + 600) = ( EBIT-6 000×6%-2 400×8%) ×(1 - 25% )/3 000
兩邊約掉1-25%
(EBIT-6 000×6%) /3600= ( EBIT-6 000×6%-2 400×8%) /3 000
兩邊同時(shí)乘3600
(EBIT-6 000×6%) = 3600/3 000*( EBIT-6 000×6%-2 400×8%) /3 000
EBIT-360=1.2*(EBIT-360-192)
EBIT-360=1.2*EBIT-1.2*552
0.2EBIT=662.4-360=302.4
EBIT=302.4/0.2=1512
2023 09/04 13:41
![](/wenda/img/newWd/sysp_btn_eye.png)